A Audiência de apresentação do adolescente no procedimento de apuração do ato infracional: o direito à ampla defesa e ao contraditório face a ótica garantista do Estatuto da Criança e do Adolescente - RODRIGUES, Jenifer Natasha Sodre (2022)
This paper discusses the implications of a adolescent deposition at the presentation hearing in the investigating procedure of a crime commited by him, and the applications of the adversarial principle and legal defense. It is a modern legal institute in brazilian law, in order to analyze the aforementioned procedure, sought to make a parallel with the constitutional guarantees and international treaties and declarations ratified by Brazil, and also the forms of application already adopted in criminal proceedings. Therefore, it was necessary to approach the handling of children and adolescents from the historical and normative perspective; present the investigating procedure’s steps of crimes commited by a minor, demonstrate the presentation hearing as a specific institute in the juridical area dedicated to children and adolescent, correlating with effectuation of constitutional guarantees in that step. We begin with a deductive approach by bibliographic and documentary research. That said, it was found that the Constitution is clear when determines the adversarial principle and legal defense in the brazilian legal system. It was also observed that the Code of Criminal Procedure during its term adapted to the changes adhered to in the new constitutional system, molding itself for this. It turns out, that the adolescent deposition at the presentation hearing in the investigating procedure of a crime commited by him, as a first step, go against the constitutional principles and guarantees already enshrined.